Advances of Olfactory Design and Its Applications in Library Studies - YU Yingying, SU Wencheng, WU Junru (Nongye tushu qingbao xuebao, 2022)
[Purpose/Significance] The olfactory experience can influence human emotion and cognition. Space olfactory design enhances our overall activity experience and satisfaction with the whole space environment by awakening our positive emotional feelings and promoting the positive nature of behavioral activities. It provides reference and inspiration for the application of spatial olfactory design in public cultural service institutions such as libraries. Therefore, the utility of the olfactory experience for users can be applied to library architectural spaces, so as to increase the loyalty of library users. [Method/Process] This paper used literature research and content analysis method to collect, screen, organize and analyze the related literature on space olfactory design at home and abroad, to review the domestic and international research on the role of space olfactory, and to summarize the research progress and application trends of space olfactory design at home and abroad. The practical application of space olfactory design and the utility of space olfactory experience were analyzed, including the role of space odor design on emotional arousal, memory utility of space-related events and on other sensory behavioral efficiency enhancement, behavioral performance improvement and learning memory capacity improvement. [Results/Conclusions] The study found that international research scenarios on the design of space olfactory were focused mainly on the olfactory experience in special contexts such as learning scenarios and commercial shopping scenarios. In contrast, domestic research on space olfactory design is still at the stage of theoretical exploration, and the empirical research is yet to be explored. Scent marketing in commercial field provides theoretical and practical guidance for library space scent environment design. In addition, in order to create future learning centers based on the perspective of the user's olfactory experience, public libraries need to pay more attention to the consistency of scent with the library's reading space, learning center and cultural and leisure center and other space services, and the mechanism of the influence of the space scent on the subjective emotional feelings of library users and their reading experience, learning behavior and recreational and leisure activities in the libraries. The olfactory sensitivity and olfactory preference of library user groups and librarian groups are the issues that must be considered to realize the olfactory design of library space and are the prerequisites for building a human-oriented library. In addition, based on the spatial activity needs of university libraries, our study can be used as a pilot for library space olfactory design.